Lyme disease: the present status - Cabral, Ana (1997)
Lyme disease is a complex multisystemic disorder with a rising incidence worldwide. It is a tick-borne infectious disease caused by a newly recognized spirochete, Borrelia burgdorferi. Lyme disease may mimic and should be differen ciated from other immune-mediated disorders as its symptoms may include neurologic, joint, eye or cardiac abnormalities, as well as the typical skin lesion. The authors describe some new concepts on epidemiology, and clinical characteristics of the disease as well as its diagnosis and treatment.